Return to the Big Valley : [large type] 3 romances from a unique Pennsylvania Amish community - Brunstetter, Wanda E.; Brunstetter, Jean; Brunstetter, Richelle (Center Point Large Print, 2021)
"Journey back to an area of Pennsylvania that is home to three distinct Amish communities and meet three young women who face heartfelt disappointments in romance. Wilma's Wish by Wanda E. Brunstetter Wilma Hostetler has been courted by Israel Zook for the last year, and he's recently proposed marriage. But when his sister dies, leaving him to care for five young nephews who openly dislike Wilma, she has second thoughts of starting with a ready-made family and decides to call off the wedding. Can anything be done to restore the relationship, or will Israel seek another wife? Martha's Miracle by Jean Brunstetter Martha Yoder is different from other Amish women in her love of hunting and the outdoors. Meeting Glen Swarey, who is working with the local fire department, seems to be a good match. But can Martha accept Glen's thoughts of leaving the Amish faith, or will she walk away from a chance at love? Alma's Acceptance by Richelle Brunstetter Alma Wengerd is a young widow who leaves her home in Kentucky to stay with friends in Pennsylvania. Soon she is speeding into a renewed romance with Elias Kurtz and raising the brows of the older church members. When Alma is waylaid by some unexpected news, could putting her happiness with Elias on hold be her only option?"--